External representations in ubiquitous computing design and the implications for design tools. - Dow, Steven; Saponas, Scott; Li, Yang; Landay, James A. (Proceedings of the 6th ACM Conference on Designing interactive Systems, 2006)
One challenge for ubiquitous computing is providing appropriate tools for professional designers, thus leading to stronger user-valued applications. Unlike many previous tool-builders’ attempts to support a specific technology, we take a designer-centered stance, asking the question: how do professional designers externalize ideas for off-the-desktop computing and how do these inform next generation design tools? We report on interviews with designers from various domains, including experience, interaction, industrial, and space designers. The study broadly reveals perceived challenges of moving into a non-traditional design medium, emphasizes the practice of storytelling for relating the context of interaction, and through two case studies, traces the use of various external representations during the design progression of ubicomp applications. Using paperprototyped “walkthroughs” centered on two common design representations (storyboards and physical simulations), we formed a deeper understanding of issues influencing tool development. We offer guidelines for builders of future ubicomp tools, especially early-stage conceptual tools for professional designers to prototype applications across multiple sensors, displays, and physical environments.